Analisa Emisi Gas Buang Nissan X -Trail dengan Bahan Bakar Pertalite Dengan Penambahan Ethanol Dan Pertamax - ., Ponidi; D S Putri, Ida Ayu (Rekayasa Material, Manufaktur dan Energi, 2022)
Vehicle exhaust emissions greatly affect the environment and human health. The fuel used in the vehicle is very influential on the results of these exhaust emissions. In Indonesia itself, the most frequently used gasoline fuel is pertalite fuel with an octane rating of 90. The purpose of this study is to compare the results of exhaust gas emissions from pure pertalite fuel, the addition of ethanol to pertalite fuel and pure pertamax. And as a reference, namely the Regulation of the State Minister of the Environment number 05 of 2006 concerning the threshold value of the exhaust gas emission threshold issued by gasoline-fueled motor vehicles. Ethanol itself is a high octane fuel and can be used to add octane rating to gasoline. Ethanol can also be used as an alternative fuel and is relatively safer for the environment. Ethanol itself can absorb moisture in the fuel tank. The addition of 10% ethanol can increase the octane rating by approximately 3 points. The octane number of ethanol is also greater than pertalite fuel. The results of this study indicate that there is an effect on the addition of ethanol to pertalite fuel with a ratio of 1: 4, namely 20% ethanol and 80% pertalite. The addition of ethanol can reduce the results of CO and HC in the exhaust gas emissions it self.